173k views
19 votes
The expression (x^13)(x^6) is equivalent to x^p. What is the value of p?

1 Answer

5 votes

Answer:

p=19

Explanation:

since the instructions say that (
x^(13))(
x^(6)) is equivalent to
x^(p), we can make the equation:

(
x^(13))(
x^(6))=
x^(p)

now, apply the laws of exponents;
a^(m) * a^(n) =a^(m+n)

in that case, since we're multiplying x to the 13th power by x to the 6th, the result is
x^(13+6), which is
x^(19)

the equation now:


x^(19)=
x^(p)

since the exponents are at the same base, we can solve the equation

19=p

so p is 19

hope this helps :)

User Joshua DeWald
by
4.9k points